2017
DOI: 10.1111/jcmm.13444
|View full text |Cite
|
Sign up to set email alerts
|

Negative HBcAg in immunohistochemistry assay of liver biopsy is a predictive factor for the treatment of patients with nucleos(t)ide analogue therapy

Abstract: The hepatitis B core antigen (HBcAg) is an important target for antiviral response in chronic hepatitis B (CHB) patients. However, the correlation between HBcAg in the hepatocyte nucleus and nucleos(t)ide analogue (NA) therapeutic response is unclear. We sought to evaluate the role of HBcAg by analysing liver biopsies for viral response in NA‐naïve hepatitis B e antigen (HBeAg) positive (+) CHB patients via immunohistochemistry (IHC). A total of 48 HBcAg‐negative (−) patients and 48 HBcAg (+) patients with mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Due to the fact that different staining patterns of the HBcAg IHC may reflect differences in the histological activity and viral replication [ 48 50 ], the IHC staining pattern was confirmed by a second automated IHC. Together these results suggested that these necropsied cats may be at a chronic stage of the infection, supported by the histological feature of hepatic fibrosis and low DCH viral copy number in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that different staining patterns of the HBcAg IHC may reflect differences in the histological activity and viral replication [ 48 50 ], the IHC staining pattern was confirmed by a second automated IHC. Together these results suggested that these necropsied cats may be at a chronic stage of the infection, supported by the histological feature of hepatic fibrosis and low DCH viral copy number in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining of the liver tissue section is another general method to measure chronic hepatitis B patients [41]. The presence of HBcAg in nuclear hepatocytes indicates an active viral replication.…”
Section: Establishment Of Home-made Sandwich Elisamentioning
confidence: 99%